THE ROLE OF THE HEALTH SERVICE (DINKES) IN PREVENTING CASES OF STUDENT SUICIDE DEATHS IN BANDA ACEH - Lailatul Hasanah; Muazzinah; Cut Zamharira (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The implementation of this study is aimed at looking at the role of the Banda Aceh City Health Office in preventing and controlling suicide cases using qualitative methods with descriptive research types. Informants in this study were the TK I/IIID Entemonologist Health Expert Young Field of Disease Prevention and Control of Mental Illness Control Section of the Banda Aceh City Health Office, as well as several stakeholders in Banda Aceh City, and data collection techniques in this study were carried out through interviews, observation, and documentation. The results of this study concluded that the role of the Banda Aceh City Health Office in preventing and controlling suicide cases was considered effective administratively and in action, but there were still some shortcomings in special programs, as well as data on satisfaction with government regulations, the achievement of overall objectives in the implementation of prevention and control of suicide cases carried out by the Banda Aceh City Health Office. This can be seen from several cases of student suicide deaths, this situation claimed several student victims in Banda Aceh, this can happen because stakeholders do not feel that there is a related role, the cases that arise are considered as a lack of faith in the perpetrators of suicide themselves, so that there is a blurring of the role of stakeholders that is seen in the aspect of prevention and control of student suicide cases in Banda Aceh, however, the Banda Aceh City Health Office has a special program to handle the mental health and soul of students in Banda Aceh in the new semester, socialization of mental health and mental health is carried out at every campus in Banda Aceh. The suggestions that the author provides are based on the research results found, especially to the Banda Aceh City Health Office to be more sensitive to the issue of student deaths in Banda Aceh because it is very possible that some of the deaths that occur are a solution for students to end their life problems, and for the Banda Aceh City government to budget funds to carry out socialization related to the prevention and control of suicide cases to campuses in Aceh, especially in Banda Aceh City, at least once a year, and it is hoped that they will provide consultation services or call centers.